2015
DOI: 10.1111/trf.13434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood transfusion on intestinal blood flow and oxygenation in extremely preterm infants during first week of life

Abstract: Blood transfusion increased blood pressure and intestinal tissue oxygenation but did not alter blood flow velocities. Partial feeding had no impact on intestinal blood flow and tissue oxygenation changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In support of this, EPO has been shown to be protective against NEC [42-44] and one of the hypotheses for this protective effect is secondary to prevention of anaemia of prematurity. Recent Cochrane analyses of early [77] and late [52] rEPO usage concluded that there was a reduction in the number and volume of RBCT but the clinical significance was questioned.…”
Section: Anaemia Blood Transfusion and Necmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, EPO has been shown to be protective against NEC [42-44] and one of the hypotheses for this protective effect is secondary to prevention of anaemia of prematurity. Recent Cochrane analyses of early [77] and late [52] rEPO usage concluded that there was a reduction in the number and volume of RBCT but the clinical significance was questioned.…”
Section: Anaemia Blood Transfusion and Necmentioning
confidence: 99%
“…Seidel et al [38] measured crSO 2 and prSO 2 before, during, immediately after, and 24 h after RBCT and noticed a significant improvement in cerebral and peripheral tissue oxygenation and perfusion (correlating with improvement in clinical symptoms of anaemia) upon transfusing those with crSO 2 < 55% compared to ≥55% [38]. Banerjee et al [43, 44] reported that RBCT improves cerebral and gut tissue oxygenation in preterm infants of any post-natal age irrespectively of the feeding pattern, the pre-transfusion Hb, or the presence or absence of PDA [43, 44]. …”
Section: Blood Transfusion and Peripheral Brain And Gut Perfusionmentioning
confidence: 99%
“…Bhalala et al ( 29 ) reported a decrease of 20 % and more compared to the baseline values. NIRS was recommended to determine the oxygen demand of regional oxygen saturation (rSO 2 ), transfusion requirement, and in the diagnosis of necrotizing enterocolitis (NEC) in neonatal intensive care units ( 5 , 30 32 ). Kaufman et al ( 33 ) found a strong correlation between splanchnic rSO2 and gastric pH measurement, mixed venous oxygen saturation, and serum lactate levels in 20 infants who underwent congenital cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The NIRS analysis was completed in 5 minute epochs and any areas within the 60 minute recording deemed to be "noisy" were removed from the analysis under the guidance of a medical physicist in NIRS (TSL). In most NIRS studies around 10% of infants are excluded because of motion artefacts 12,42 , but no baby was excluded because of motion artefact from the present study.…”
Section: Strengths Of the Studymentioning
confidence: 99%